2022
DOI: 10.1093/jmcb/mjac071
|View full text |Cite
|
Sign up to set email alerts
|

Intraneuronal tau aggregation induces the integrated stress response in astrocytes

Abstract: Progressive aggregation of tau protein in neurons is associated with neurodegeneration in tauopathies. Cell non-autonomous disease mechanisms in astrocytes may be important drivers of the disease process but remain largely elusive. Here, we studied cell type-specific responses to intraneuronal tau aggregation prior to neurodegeneration. To this end, we developed a fully human co-culture model of seed-independent intraneuronal tau pathology, which shows no neuron- and synapse loss. Using high-content microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…In contrast, expression of double mutated FTDtau 1+2 led to the formation of tau aggregates that did not require seeding. These data, as well the data presented in our primary research paper (Batenburg et al., 2022), demonstrate the feasibility of FTDtau 1+2 to model tau aggregation without the use of seeds that have thus far been a requirement for the induction of tau aggregation in human iPSC‐derived neurons (Verheyen et al., 2015). In addition, we have showed that expression of FTDtau 1+2 induces tau aggregation in a three‐dimensional neuron/astrocyte co‐culture (Batenburg et al., 2023), highlighting the versatility of this approach to induce spontaneous tau aggregation in more advanced cell culture models.…”
Section: Commentarysupporting
confidence: 66%
See 2 more Smart Citations
“…In contrast, expression of double mutated FTDtau 1+2 led to the formation of tau aggregates that did not require seeding. These data, as well the data presented in our primary research paper (Batenburg et al., 2022), demonstrate the feasibility of FTDtau 1+2 to model tau aggregation without the use of seeds that have thus far been a requirement for the induction of tau aggregation in human iPSC‐derived neurons (Verheyen et al., 2015). In addition, we have showed that expression of FTDtau 1+2 induces tau aggregation in a three‐dimensional neuron/astrocyte co‐culture (Batenburg et al., 2023), highlighting the versatility of this approach to induce spontaneous tau aggregation in more advanced cell culture models.…”
Section: Commentarysupporting
confidence: 66%
“…Because FTDtau 1 and FTDtau 1+2 are both mutated tau variants that differ in tau aggregation, FTDtau 1 is a feasible control for overexpression of mutant tau to ascertain that cellular effects in the co‐culture are due to tau aggregation. This, in combination with a high‐content microscopy approach that was previously validated in our laboratory (van Ziel et al., 2020; Wolzak et al., 2022), enabled us to quantify and target the timing, extent, and cell (non)autonomous effects of spontaneous intraneuronal tau aggregation in a standardized manner in thousands of cells (Batenburg et al., 2022). This indicates that this rapid, miniaturized, and standardized model is a powerful tool for the preclinical screening of tau‐targeting therapeutics.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Since this may be a confounding factor for the investigation of how tau pathology within neurons affects their interaction with astrocytes in the 3D culture, we adopted a novel approach for seed-independent tau pathology using double mutant FTDtau 1+2 . This approach previously enabled seed-independent tau pathology in rodent brain slice cultures [ 29 ] and a 2D human neuron/astrocyte co-culture [ 8 ]. In agreement, neuron-specific expression of FTDtau 1+2 induces intraneuronal MC1-positive tau pathology within 4 weeks in the 3D co-culture.…”
Section: Discussionmentioning
confidence: 99%
“…The physical and functional interaction between these cell types, for example at tripartite synapses, is critical for brain physiology and plays an important, yet not fully understood role in neurodegeneration [ 7 ]. Recently our group developed a two-dimensional (2D) hiPSC-derived neuron/astrocyte co-culture model for tau pathology, to study cell non-autonomous effects of intraneuronal tau pathology [ 8 ]. Although hiPSC-derived neural cultures contributed to our understanding of neuron and astrocyte physiology, they lack the natural interactions in the brain micro-environment.…”
Section: Introductionmentioning
confidence: 99%